Identifikasi dan Peran Ekologis Kiambang (Pistia stratiotes) Sebagai Makroflora Perairan Pada Ekosistem Perairan Tergenang - Waruwu, Risda Mawarni (CV. SINAR HOWUHOWU, 2025)
This study aims to explore the morphology and ecological functions of kiambang (Pistia stratiotes) as macro flora in stagnant aquatic ecosystems. The research was conducted through direct observation in an earthen pond in Mazingo Tabaloho Village with a descriptive approach. Observations revealed that Pistia stratiotes has characteristics such as light green leaves arranged in a rosette, hanging fibrous roots, and a floating growth method. This plant plays a significant role in absorbing excessive nutrients and heavy metals, while providing shelter for small organisms, thus supporting the balance of aquatic ecosystems. However, overpopulation can cause water quality degradation by covering the surface and reducing dissolved oxygen levels. Understanding the characteristics and ecological role of kiambang is key to supporting sustainable management of stagnant waters.